A Study Of The Profile Risk, Factors And Knowledge, Attitude And Practice Of Women With Breast Cancer In Kelantan. - Bachok, Noorsaadah (2001)
Breast cancer is the commonest female cancer in the world with Malaysian prevalence of 86.2 per 100,000 women in 1996. There was an increasing trend of breast cancer mortality rate in Malaysia from 0.61 in 1983 to 1.8 per 100,000 populations in 1992. This study was aimed to identify profile, risk factors of breast cancer and to compare the level of knowledge, attitude and practice regarding breast cancer between cases and controls. A matched case-control study was carried out at hospitals in Kelantan. A standardized questionnaire was used to interview 147 histologically confirmed breast cancer patients and 147 controls. Controls were non-breast cancer patients who were matched for age and ethnicity of cases and non-malignant, non-gynaecologicaf, non-hormonal and non-endocrinological patients. Potential risk factors and score of knowledge, attitude and practice were initially analysed by simple conditional logistic regression and paired t test. Multiple conditional logistic regression modelling was later used to control potential confounding factors. The mean age of breast cancer patients was 46.3 :!: 9.3 years. The most common histological type was infiltrative ductal carcinoma (73%). Presentation at stage "' and VI was 60%. Factors contributing towards increased risk of breast cancer were nulliparity (Odds Ratio (OR) 42.6, 95% Confidence Interval (95% CI) 4.8-380.8), having one or two children (OR 2.2, 95% CI 1.0-5.0), family history of breast cancer (OR 4.2, 95% CI 1.4-12.8) and ever taken oral contraceptives (OC) (OR 2.8, 950/0 CI 1.4- 5.8). Cases had significantly better score of knowledge than controls (paired t test =4.9, p<O.001). There were no significant differences between cases and controls in total scores of attitude (paired t test =0.6, p>0.05) and practice (paired t test = -0.7, p>0.05). Less than 200/0 of cases and controls practised monthly Breast Self-Examination (8SE). This study included younger pre-menopausal women. The profile of breast cancers such as age and ethnic distributions was different from other studies. This study reconfirmed that similar risk factors identified in western population were responsible for the occurrence of breast cancer in Kelantan. It also supported the theory that breast cancer occurrence was related to oestrogen exposure and familial factors. It suggested the importance of having children especially more than two and caution for OC users and women with family history of breast cancer. Significant higher level of knowledge did not ensure positive attitude and better practice. Health education is needed especially for high-risk women in order to change their attitude and facilitate regular correct method of screening for breast cancer.